The relation of lyric function melody and harmony case study: oh pretty woman by Roy Orbison / Sarita Daiman - Daiman, Sarita (2010)
The purpose of this thesis is to gather intonation that found Roy Orbison composition, The composition were analyze with the objective of determining the relation 01 lyric and music function in Roy Orbison's composition. The song is Oh Pretty Women that have been. composed in year 1964. In lyric writing, they are certain factor that should be considered and can be analyzed, Therefore, the author will do a research the analysis presented will consist of lyric analysis and relate it with music function whether If its support each other hand does this composition support the film Pretty Women. ln order to, the author more concerned on the composition analysis especially the craft of lyric writing and the relationship between them he methodology could be modified to fit the objective.